VD_FINDINFO HC / 2013 / 796 vom 3. Dezember 2013 - VD Tribunal cantonal (2013)
PREUVE À FUTUR, DÉCISION SUR FRAIS, DÉPENS | 110 CPC (CH), 158 al. 2 CPC (CH), 319 let. b ch. 1 CPC (CH), 95 al. 1 CPC (CH)